Proof of the BMR conjecture for G20 and G21. (May 2019) - Marin, Ivan
Abstract: We prove two new cases of the Broué–Malle–Rouquier freeness conjecture for the Hecke algebras associated to complex reflection groups, using methods inspired by non-commutative Gröbner bases. These two cases are the complex reflection groups of rank 2 called G 20 and G 21 in the Shephard and Todd classification. This reduces the number of remaining unproven cases to 3.